1993
DOI: 10.1007/bf02231562
|View full text |Cite
|
Sign up to set email alerts
|

Elevated anticardiolipin antibodies in a patient with vibration-white-finger, valvular heart disease and psoriatic arthritis

Abstract: We describe a case of irreversible severe vibration-white-finger (VWF) occurring in a male who used a compression-hammer daily at work for a 20-year period. Infra-red thermography following either a cold provocation or a vibratory stress was a sensitive objective method of documenting the condition. Persistent elevation of IgG anticardiolipin antibodies (aCL) was found in his serum and may be a marker of endothelial damage associated with either VWF or the patient's coincidental valvular heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…IRT has been successfully used in the diagnosis and assessment of recovery after treatment in Raynaud's phenomena [52,[172][173][174], gout [175] and arthritis [176,177]. Arnold et al reported that, IRT is an excellent technique for measurement of skin temperature over different joints [178].…”
Section: Diagnosis Of Rheumatic Diseasesmentioning
confidence: 99%
“…IRT has been successfully used in the diagnosis and assessment of recovery after treatment in Raynaud's phenomena [52,[172][173][174], gout [175] and arthritis [176,177]. Arnold et al reported that, IRT is an excellent technique for measurement of skin temperature over different joints [178].…”
Section: Diagnosis Of Rheumatic Diseasesmentioning
confidence: 99%
“…Um tipo especial de doença reumática de interessante avaliação infravermelha é a artrite psoriásica, que tem sido objeto de diferentes estudos (54)(55)(56) .…”
Section: Artrite Psoriásicaunclassified
“…Infrared thermography technique (IRT) is utilized by a growing number of disciplines within medicine (1)(2)(3)(4). IRT is considered as a non-invasive scanning thermometer.…”
Section: Introductionmentioning
confidence: 99%